2012
DOI: 10.4238/2012.may.18.1
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the effects of androgen receptor gene trinucleotide repeats and prostate-specific antigen gene polymorphisms on prostate cancer

Abstract: ABSTRACT. The number of trinucleotide repeats [CAG (coding for polyglutamine), GGC (coding for polyglycine)] in the first exon of the androgen receptor (AR) gene and prostate-specific antigen (PSA) gene androgen response element I A/G polymorphism are both related to prostate cancer prognosis. We investigated whether these genomic changes occur in the AR and PSA genes, which are usually found in individuals with prostate cancer, of Turkish patients and to find out their distribution in the population. We used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 32 publications
1
8
1
Order By: Relevance
“…By contrast, some studies did not identify an association with this repetition [43, 95, 96]. Several studies reported no association between the GGC repeat lengths, the PC risk, and pathological characteristics [34], stating that there were no significant differences between cases and controls [97]. Similarly, the risk of PC and the tumor characteristics did not differ in relation to the number of GGC repeats in this study [93].…”
Section: The Androgen Receptor (Ar) Gene and Prostate Cancer Riskcontrasting
confidence: 64%
“…By contrast, some studies did not identify an association with this repetition [43, 95, 96]. Several studies reported no association between the GGC repeat lengths, the PC risk, and pathological characteristics [34], stating that there were no significant differences between cases and controls [97]. Similarly, the risk of PC and the tumor characteristics did not differ in relation to the number of GGC repeats in this study [93].…”
Section: The Androgen Receptor (Ar) Gene and Prostate Cancer Riskcontrasting
confidence: 64%
“…The principal characteristics of included studies are listed in Table 1. Genotype distribution in controls was corresponded to HWE in all but one study [18]. …”
Section: Resultsmentioning
confidence: 99%
“…On the contrary, Abha Soni et al insisted that the genotypes AA and GA of this polymorphism were significantly related to elevated risk of BPH in their study involving 120 BPH cases and 105 controls in Indians [21]. Whereas, a study by Alptekin and colleagues detected no statistically significant difference in the frequencies of genotypes or alleles of PSA -158G/A polymorphism between controls and BPH cases in Turks, suggesting that the polymorphism might not have independent influence on the disease onset [18]. …”
Section: Disscussionmentioning
confidence: 99%
“…There are numerous studies on HSV-TK suicide genes, 5-FC+GCV prodrug therapy, NTR/CB1954, and nitro reductase system on prostate cancer. Several biomarkers including prostatespecific antigen (PSA), prostate-specific membrane antigen (PSMA), androgen, C-X-C chemokine receptor type 4 (CXCR4), and epithelial cell adhesion molecule (EpCAM) have been identified for prostate cancer [82][83][84] . Consequently, promoters of the aforementioned genes are incorporated into the constructs of cancer suicide genes, which are expressed in prostate cancer cells [61,65] .…”
Section: Clinical Applicationsmentioning
confidence: 99%